2015
DOI: 10.1039/c4ta06777k
|View full text |Cite
|
Sign up to set email alerts
|

High energy density titanium doped-vanadium oxide-vertically aligned CNT composite electrodes for supercapacitor applications

Abstract: In this study, we provide the first report on the supercapacitance behavior of titanium doped vanadium oxide films grown on vertically aligned carbon nanotubes using a chemical vapor deposition (CVD) technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 128 publications
1
29
0
Order By: Relevance
“…4,5 Ever since their discovery, because of the special structural, mechanical, electronic and fast electron transfer properties, CNTs have gained substantial attention in electronic applications. [8][9][10][11][12] However, only a few studies have reported on glucose sensors based on Co 3 O 4 . [9][10][11][12][13][14][15][16] Generally these metal oxide based sensors directly electrooxidise the glucose mediated by M 2+ /M 3+ (M = metal) in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Ever since their discovery, because of the special structural, mechanical, electronic and fast electron transfer properties, CNTs have gained substantial attention in electronic applications. [8][9][10][11][12] However, only a few studies have reported on glucose sensors based on Co 3 O 4 . [9][10][11][12][13][14][15][16] Generally these metal oxide based sensors directly electrooxidise the glucose mediated by M 2+ /M 3+ (M = metal) in alkaline medium.…”
Section: Introductionmentioning
confidence: 99%
“…But among such energy storage systems electrochemical capacitors or supercapacitors have drawn attention as one of the most promising energy storage systems because of their high power density, short charging time and long life span although having moderate energy density 10-15 mWh/g which is still very less compared to batteries. Different research groups in the world are trying to improve the energy density and overall life span of the device by suitably choosing different electrode materials [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many mixed valence VO x have been discovered for pseudocapacitors, such as V 2 O 3 / rGO/VO 2 , [199] V 2 O 3 /VO 2 @C, [200] hydrated VO x (2 < x < 2.5), [201] hydrated V 6 O 13 /V 2 O 5 , [202] VO x (1.5 < x < 2.5), [203] and Ti-doped VO x (2 < x < 2.5). [204] However, it was difficult to tell what the influence of different oxidation states is.…”
Section: Vanadium Oxide Nanocomposites In Pseudocapacitorsmentioning
confidence: 99%